2023
DOI: 10.1002/adma.202211632
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Quenching NIR‐II J‐Aggregates of Benzo[c]thiophene Fluorophore for Highly Efficient Bioimaging and Phototheranostics

Abstract: Molecular fluorophores with the second near‐infrared (NIR‐II) emission hold great potential for deep‐tissue bioimaging owing to their excellent biocompatibility and high resolution. Recently, J‐aggregates are used to construct long‐wavelength NIR‐II emitters as their optical bands show remarkable red shifts upon forming water‐dispersible nano‐aggregates. However, their wide applications in the NIR‐II fluorescence imaging are impeded by the limited varieties of J‐type backbone and serious fluorescence quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The absorption spectrum of 2TP-BBT in the solid state exhibits a significant red shift compared to that in the solution state. Remarkably, the absorption spectra of 2TP-BBT in tetrahydrofuran (THF) solution with different water contents showed that 2TP-BBT exhibited a redshift tendency with increasing water content, which indicated the formation of a J aggregated state 48–50 (Fig. S4, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…The absorption spectrum of 2TP-BBT in the solid state exhibits a significant red shift compared to that in the solution state. Remarkably, the absorption spectra of 2TP-BBT in tetrahydrofuran (THF) solution with different water contents showed that 2TP-BBT exhibited a redshift tendency with increasing water content, which indicated the formation of a J aggregated state 48–50 (Fig. S4, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, benzo­[ c ]­thiophene was found to be a perfect candidate to construct NIR-II AIEgens owing to its rich electron-donating feature for lowering band gap and large steric hindrance for guaranteeing AIE characteristics. Herein, we designed three butterfly-shaped analogues, namely, 4TPA-TQ, 2TPA2TPE-TQ, and 4TPE-TQ in those benzo­[ c ]­thiophene units were utilized as an electron-rich donor/π-bridge, thiadiazolo [3,4- g ] quinoxaline (TQ) acted as an electron acceptor, and four TPA and/or TPE units connected on the periphery of fluorophores served as molecular rotors. As classical building blocks of AIEgens, the TPA/TPE moieties on one hand are advantageous to suppress the fluorescence quenching effect as nanoaggregates according to the mechanism of restriction of intramolecular motions (RIM) .…”
Section: Resultsmentioning
confidence: 99%
“…18 AIE fluorescent probes have been designed for imaging atherosclerotic plaques based on pathology. 19,20 For example, the excessive accumulation of ox-LDL triggers the formation of lipid droplets (LDs) in foam cells, a hallmark of AS. 21,22 These AIEgens, however, could nonspecifically stain other lipid-laden organelles and tissues (e.g., arterial walls and fatty liver), making them impractical for precise identification of the plaques for the potential clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence imaging has become as an indispensable modality because of its high sensitivity, excellent spatial resolution, and fast acquisition and image processing. , Recently, aggregation-induced emission luminogens (AIEgens) are an alternative class of fluorescent molecules, which are nonemissive when dissolved but strongly fluorescent in the aggregated state . AIE fluorescent probes have been designed for imaging atherosclerotic plaques based on pathology. , For example, the excessive accumulation of ox-LDL triggers the formation of lipid droplets (LDs) in foam cells, a hallmark of AS. , These AIEgens, however, could nonspecifically stain other lipid-laden organelles and tissues (e.g., arterial walls and fatty liver), making them impractical for precise identification of the plaques for the potential clinic. , …”
Section: Introductionmentioning
confidence: 99%